Chokepoint: Regulating US student mobility through biometrics. (May 2015) - Nguyen, Nicole
Abstract: Many US public schools, struggling with perceived issues of safety and security, have installed a host of different biometric devices – vein scanners, automated fingerprint identification systems, iris scanners, GPS-enabled identification badges, and facial recognition software. Schools turn to these devices in hopes of securing school space by sorting and tracking students, visitors, and school staff based on their pre-determined risk profiles. As such, this article proposes that tracing these new forms of school security provides insight into how the politics and practices of biometric technologies are fundamentally geographical in nature. That is, biometric devices not only verify identity according to risk assessments, they also work to manage mobility by regulating where school bodies can go, when, and for what purposes. Moreover, this article analyzes how these risk profiling tactics, widely adopted by schools across the United States, necessarily borrow from the strategies used in sites of colonial occupation. Looking at schools in this way can help us plot how biometric bordering and resultant security decisions unfold at other sites of mobility beyond state (smart) borders, highways, toll booths, and ports of entry in order to formulate new "spaces of enclosure" (Amoore, Marmura, & Salter, 2008) and "dividing practices" (Nevins, 2002), thus bringing students into "closer proximity" to military relations of force through these "war-like architectures" (Amoore, 2009). Highlights: Schools are an understudied site of biometric tracking and monitoring. Schools provide insight into how biometrics not only verify identity, but also regulate micro-forms of mobility. Biometrics are fundamentally geographical in nature. The logic of preemption organizes strategies of school security.